Decadal modulation of ENSO and IOD impacts on the Indian Ocean upwelling - Zhang, Xiaolin; Mochizuki, Takashi (Frontiers in Earth Science, 2023)
The decadal modulations are observed in impacts of El Niño and Southern Ocean (ENSO) and Indian Ocean Dipole (IOD) on the tropical Indian Ocean upwelling. Here, we explore important contributors to the decadal modulations by combining the observational data since 1958 and statistical model simulations. A Bayesian Dynamic Linear Model (BDLM), which represents the temporal modulations of the IOD and ENSO impacts, reproduces the timeseries of the eastern and western Indian Ocean (EIO and WIO) upwellings more realistically than a conventional Static Linear regression Model does. The time-varying regression coefficients in BDLM indicate that the observed shift of the IOD impact on the EIO upwelling around 1980 is mainly due to the changes of alongshore wind stress forcing and the sensitivity of the upper ocean temperature in the EIO through the surface warming tendency and the enhanced ocean stratification. In contrast, the impacts of ENSO and IOD on the WIO are modulated in relation to the decadal variability of the tropical Pacific Ocean. When the eastern tropical Pacific Ocean is observed warmer on decadal timescales, the accompanying changes of the dominant ENSO flavors contribute to modulating the strengths of the atmospheric convective activity over the Indian-Pacific warm pool and the easterly wind variations in the equatorial Indian Ocean.